DEVELOPMENT OF ECONOMIC RELATIONS BETWEEN KAZAKHSTAN AND SINGAPORE: RESULTS OF THIRTY YEARS OF PARTNERSHIP - Akylbay А.; Argyngazinov, A. (Journal of Oriental Studies, 2025)
In 2024, Kazakhstan and Singapore celebrated the 30th anniversary of the establishment of bilateral relations. Over the years, the countries have built strong and reliable relations based on trust and mutual respect, indicating overall stability. Since 1993, several significant developments have occurred in the bilateral relations between Kazakhstan and Singapore, especially in their respective build-up of material potential, strengthening of institutional contacts and expansion of economic ties. Economic cooperation between the Republic of Kazakhstan and the Republic of Singapore is one of the key elements in strengthening the ties between Central Asia and Southeast Asia. Both countries have a strategic geographical location and are committed to diversifying their economies, which creates a solid foundation for mutually beneficial partnership. This article describes the main developments in the bilateral relations between these countries and how bilateral interstate relations have flourished in the field of economy. The authors tried to assess the joint economic projects of the two countries and trade between them by analyzing government documents and the media. Keywords: Singapore, Kazakhstan, bilateral relations, economic relations.